River restoration via CAP eco-schemes: current support and future opportunities for blue infrastructure - Pereira Dos Santos, Leonor; Birk, Sebastian; Ferreira, Maria Teresa (Frontiers in Environmental Science, 2025)
Freshwater ecosystems across Europe face significant degradation, with agricultural practices playing a central role. The 2023–2027 Common Agricultural Policy (CAP) introduces new eco-schemes that could support river restoration, a key goal of EU environmental legislation. This study presents a systematic analysis of eco-schemes in all 27 EU CAP Strategic Plans, assessing their alignment with river restoration goals. We reviewed over 130 approved eco-schemes, classifying them according to their potential to support eleven predefined restoration actions (e.g., floodplain reconnection, instream habitat improvement). Support was categorized as direct, indirect, potential, or not supported. The analysis combined AI-assisted text processing with manual validation. Results reveal considerable variation in how Member States use eco-schemes to support river restoration. While some countries offer multiple schemes with direct or indirect relevance, most focus on maintaining existing practices. Only a limited number explicitly support actions like riparian buffer restoration or wetland creation. Over 30% of all eco-schemes fall into the “potential” category, where design could be enhanced to support freshwater restoration more explicitly. Although river restoration is not a core target of CAP eco-schemes, this new instrument creates strategic opportunities to address freshwater degradation. The current implementation, however, reflects limited ambition and uneven alignment with EU water policy goals. The paper proposes adjustments to scheme design and classification methods to better embed blue infrastructure restoration within the CAP framework. This study offers the first EU-wide analysis of eco-schemes for river restoration, providing a critical baseline for future policy development and mid-term CAP revisions.